Non-Destructive Estimation of Leaf Area in Tea (Cornelia sinensis) - Zengınbal, H.; Özcan, M.; Uzun, S.; Çirak, C. (My University, 2010)
Leaf area parameters routinely measured in physiological studies provides researchers many advantages in horticultural experiments. In the present study a leaf area prediction model was developed for tea (Cornelia sinensis) by using different tea cultivars namely, Derepazari-7, Fener-3, Tuglali-10, Pazar-20, Muradiye-10, Komurculer-1 and Gundogdu-3. Leaf lamina width, length and leaf area were measured to develop the model. The actual leaf areas of the cultivars were measured by PLACOM Digital Planimeter and multiple regression analysis with Excel 7.0 computer package program was performed for the cultivars. The produced leaf area prediction model in the present study were formulized as LA=-0.66 + (0.348×L)- (0.155×L 2) - (0.133×W 2) + [1.084×(L×W)] + [0.0062×(L 2×W)J- (0.033×(W 2×C)] where LA is leaf area, W is leaf width, L is leaf length and C is cultivar. R 2 value was 0.99 for the equation. The model had also a biological meaning such as cultivars were found to be significant as a parameter in the model. © 2010 Academic Journals Inc.
Keywords: Cornelia Sinensis; Leaf Area; Modeling